Análisis comparativo del manejo técnico convencional del cultivo de quinua (chenopodium quinoa) en la economía campesina del barrio Las Lagunas del cantón Saraguro. - Mora Escudero, Josué David (2016)
This research "Comparative Analysis Of Conventional Technical Crop Management Quinoa (chenopodium quinoa) In The Peasant Economy Neighborhood Gaps Canton Saraguro" where objectives were: to determine the technical management of crop quinoa parish "Las Lagunas" canton Saraguro, determine the profitability and production costs of one hectare of land for cultivation of quinoa, make technological comparison of cultivation of quinoa based on weights, share the results with quinoa producers canton Saraguro . To fulfill the objectives set inductive, deductive and analytical method with which a summary of the observed data was performed to analyze the information they contain is used, the technique of direct observation was used, survey of farmers in the district the Lagunas, canton Saraguro, which helped us to analyze the study variables such as socio-demographic aspects, land tenure, types of production, marketing places and profitability of each production system, and the interview technicians MAGAP to determine the I support they are giving workers in the technological advancement of production for this area. The results show that 80% of farmers grow 1 hectare while 20% 2 hectares of this crop, where 87% develop quinoa in 6 months as opposed to 13% get it in 5 months, 87% of producers begins a new crop of quinoa has a production time of six months, leaving a rest time of Igul 6 months except for two producers who get their harvest in a time span of 5 months, the cereal it is mostly grown quinoa accounting for 40%, followed by wheat and barley by 20% and corn and potatoes at 10%. Quinoa byproducts are used by 75% for organic fertilizer and 25% for nutritional blocks. The most widely used type of seed is the Tunkahuan with 73% and 27% native seed. The development and maintenance of the crop producers made 72% and 28% wages. 100% of producers receive technical assistance. 47% has its own facilities for postharvest processing and 53% use leased facilities. On the marketing side, 48% sold in the local market, supermarket supplies 28%, 16% and 8% traders to shops of the town; 100% quintal quinoa sells at $ 90.00. Product losses that have occurred in the market are 37% for low output of the product from the market, 24% caused by pests. 21% due to ignorance of the product by the consumer. 12% is due to poor post-harvest handling and 6% lower prices. In the economic and productive comparative analysis of cropping systems, determining technical management in the cost of production on one hectare of land is $ 1,429,40, while traditional management in production costs amount to $ 578.25. Regarding the technical management profitability reaches 24% while traditional management reaches 4% for net profit. The system that generates better production results and increased profitability is concluded, the technical system is growing, with 24% profit compared to 4% with traditional management. Training of producers in the area is recommended, about agrotecnia crop, also developing designs records that enable them to financial analysis to determine the gain or loss and learn to deal with it to improve the quality of life producer.